People I Know: Job Search and Social Networks - Cingano, Federico; Rosolia, Alfonso (Journal of Labor Economics, 2012)
We assess the information spillovers generated by the exchange of job-related information within networks of fellow workers exploiting administrative records covering all employment relationships established in a specific local labor market over 20 years. We recover individual-specific networks of former colleagues for a sample of workers exogenously displaced by firm closures and relate their subsequent unemployment duration to the share of employed contacts at displacement date. Individual-specific networks and the longitudinal dimension of the data allow to account for most plausible sources of omitted variable bias. In particular, identification rests on within-closure within-neighborhood and within-skill comparisons conditional of a wide range of predictors for the displaced and his contacts' employment status, such as lagged wages and labor market attachment. We find that contacts' current employment rate has statistically significant effects on unemployment duration: a one standard deviation increase in the network employment rate reduces unemployment duration by about 8 percent; as a benchmark, a one standard deviation increase in own wage at displacement is associated with a 10 percent lower unemployment duration. These effects are magnified if contacts recently searched for a job and if their current employer is closer, both in space and in skills requirements, to the displaced. We find that stronger ties and lower competition for the available information also speed up re-employment. A number of specification checks and indirect tests suggests the estimated spillover effect of contacts' current employment status is driven by information exchange rather than by other interaction mechanisms.